LEXICAL VARIATION BETWEEN BOLANGITANG AND SANGKUB REGIONAL LANGUAGES IN NORTH BOLAANG MONGONDOW REGENCY - Nagita Syahwania Djenaan; Fadhil Fahrezi Manoppo; Nur Fadila Sadapu; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the lexical variation between the regional languages of Bolangitang and Sangkub in North Bolaang Mongondow Regency, North Sulawesi. This study aims to identify the differences in vocabulary between the two languages, and analyze the use of these variations in everyday communication, as well as explain the social and geographical factors that influence the emergence of lexical variations. This study uses a qualitative descriptive method. Data was collected through live interviews and online interviews with native speakers from both regions. The research instrument consists of a list of 30 basic vocabulary related to daily life, such as body parts, household activities, food, nature, and greetings. The data collected was analyzed by comparing similarities and differences in vocabulary between the two languages. The results of the study showed several lexical differences in the vocabulary commonly used by the Bolangitang and Sangkub people. Some words were found to have the same shape, while others showed differences in form and pronunciation. This variation is influenced by geographical factors, patterns of social interaction, and local language customs. This study shows that lexical variation is not only a linguistic differentiator, but also reflects the social and cultural identity of the people in North Bolaang Mongondow. Therefore, this research is expected to contribute to the documentation and preservation of regional languages in Indonesia, especially in North Bolaang Mongondow.